Smart Charging and V2G: Enhancing a Hybrid Energy Storage System with Intelligent and Bidirectional EV Charging - Thomas Franzelin; Sarah Schwarz; Stephan Rinderknecht (World Electric Vehicle Journal)
Energy storage systems and intelligent charging infrastructures are critical components addressing the challenges arising with the growth of renewables and the rising energy demand. Hybrid energy storage systems, in particular, are promising, as they combine two or more types of energy storage technologies with complementary characteristics to enhance the overall performance. Managing electric vehicle charging enables the demand to align with fluctuating generation, while storage systems can enhance energy flexibility and reliability. In the case of bidirectional charging, EVs can even function as mobile, flexible storage systems that can be integrated into the grid. This paper introduces a novel testing environment that integrates unidirectional and bidirectional charging infrastructures into an existing hybrid energy storage system. It describes the test environment in technical detail, explains the functionality, and outlines its usefulness in practical applications. The test system not only supports grid integration but also expands the degrees of freedom for testing, enabling flexible and realistic experimental setups. This environment facilitates comprehensive investigations into EV behavior, charging strategies, control algorithms, and user interactions. It provides a platform for exploring the possibilities, limitations, and optimal use cases for smart charging and hybrid storage systems in practice.